Partisipasi Masyarakat dalam Pembangunan Infrastruktur Desa di Desa Cihambulu Kecamatan Pabuaran Kabupaten Subang - Agustiani, Yuli Sri; Solihat, Hj. Yeyet (Jurnal Politikom Indonesiana, 2018)
This study uses qualitative methods using descriptive methods, using data collection techniques through observation, interviews and documentation. This research was conducted on the government of Cihambulu Village, Pabuaran Sub-District, Subang Regency, the informants of this study were 8 people, including the Cihambulu Village, Cihambulu Village Apparatus, and the Community. The results of the study are that there are still problems regarding the Pasrtisi Masyarakat in the Development of Village Infrastructure in Cihambulu Village. It was concluded that the research theory shows that community participation can be seen from the community as a tool to obtain information, community involvement, and the right to give advice, in this case there is still a need to review the participation of the community in the development of village infrastructure encourage the community to participate in this participation in Cihambulu Village Keywords: Community Participation, Infrastructure Development, Cihambulu Village